Democracy, parity and change. An institutional space for gender relations - Felipe Jaramillo Ruiz (Civilizar. Ciencias Sociales y Humanas, 2013)
In this article, I examine how gender parity is a viable mechanism to protect the capacity of transformation that characterizes democracy. Fundamentally, I contend that a democratic system needs to provide arenas of deliberation in order to contest gender relations and eradicate practices of domination. More - over, I argue that the exclusion and censorship of groups that question the predominant gender practices contradicts the spirit of democracy. Therefore, if women do not find institutional paths to express their ideas and to materialize their desires and beliefs, democratic institutions must be designed so as to en - able these processes of inclusion.